The Significant Effect of Using Phonetic-Based Materials in Teaching Pronunciation Skills in Grade XI of SMAN 1 Mataram - Hidayat, Andre; Arifuddin; Arafiq; Kamaludin (Program Studi Pendidikan Bahasa Inggris, 2025)
This research investigates the significant effect of using phonetic-based materials, particularly the International Phonetic Alphabet (IPA), in teaching pronunciation skills to eleventh-grade students at SMAN 1 Mataram. Employing a quasi-experimental design with a one-group pre-test and post-test model, the study involved 32 students from class XIF MIPA-6. Data were collected through pronunciation assessments using the Elsa Speak application, which analyzed students’ performance before and after treatment. The treatment consisted of structured lessons integrating phonetic symbols and guided practice across four meetings. The statistical analysis using a paired sample t-test showed a significant difference between pre-test and post-test scores (t = 2.275 > t-table = 2.040, α = 0.05), indicating that phonetic-based materials positively affected students’ pronunciation skills. Despite the modest increase in mean scores (from 75.8 to 76.5), the improvement was statistically significant. The study concludes that the integration of phonetic-based materials is an effective approach to enhance English pronunciation among EFL students.